ASSESSMENT OF CONATIVE CHARACTERISTICS OF YOUNG TABLE TENNIS PLAYERS - Snežana Vujanović; Branko Đukić; Mane Mirković; Mihailo Miletić; Ivana Ivanek (Sport Scientific And Practical Aspects, 2026)
The aim of this study was to analyze the conative personality traits of young table tennis players aged 15–19 years. The assessment of conative characteristics was carried out using the PIE test, completed by the best cadet boys and girls, and junior boys and girls who were preparing for the European Youth Championships in Sweden. Based on the analysis of conative dimensions, it was determined that pronounced values prevail in the dimensions of incorporation and protection, which indicates a strong need for acceptance, cooperation and respect for authority, accompanied by emotional sensitivity, tension and the possibility of developing competitive anxiety. Elevated values in the dimensions of exploration and reproduction confirm conscientiousness, planning and self-control, which is favorable for sports success. Lower values in orientation, aggression and rejection suggest good emotional and behavioral control, but also potential passivity in situations that require decisiveness, energy and combativeness in achieving one’s goals. The obtained results indicate that the emotional–conative characteristics of table tennis players represent an important segment of their sports success and that understanding these characteristics is crucial for adequate planning of psychological preparation and individualization of the training process.